Senegal : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2000)
Public consumption has declined from 12 percent of GDP in 1996 to 10.8 percent in 1999 owing to fiscal consolidation: wage increases are moderate, and other current expenditures have grown slowly. Conversely, private consumption has increased from 75.2 percent of GDP in 1996 to 76.9 percent in 1998, and is estimated to have reached 76.6 percent in 1999. Public investment has increased from 6.4 percent of GDP in 1996 to 7.2 percent of GDP in 1998 and is estimated to have reached 8.2 percent of GDP in 1999, whereas private investment has experienced a downward slide.